Shorter Cilia Length and Aberrant Ciliated Marker DNAI1 in Allergic Rhinitis - Zhou S; Liu Y; Yang Y; Huang H; Qiu Q (Dove Medical Press, 2023)
Suizi Zhou,1,2,* Yitong Liu,1,2,* Yueying Yang,1 Hongming Huang,1 Qianhui Qiu1 1Department of Otolaryngology-Head and Neck Surgery, Guangdong Provincial People's Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, People's Republic of China; 2Department of Otolaryngology, Yong Loo Lin School of Medicine, National University of Singapore, Singapore*These authors contributed equally to this workCorrespondence: Qianhui Qiu, Department of Otolaryngology-Head and Neck Surgery, Guangdong Provincial People's Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, People's Republic of China, Email qiuqianhui@hotmail.comPurpose: This study aimed to investigate whether the impaired ciliary length and aberrant ciliary ultrastructure marker, dynein axonemal intermediate chain 1 (DNAI1), are important pathological characteristics in nasal mucosa from patients with allergic rhinitis (AR).Patients and Methods: Biopsies were taken from the inferior turbinate (IT) of controls (n = 20) and patients with AR (n = 20). The ciliary length and the DNAI1 location patterns were assessed by using immunofluorescent staining. Three patterns of DNAI1 localization were defined using a semi-quantitative scoring system: normal (N), partial (P) and absence (A). Every individual section was assigned a score between 0 and 2 in each high-power field (5 fields per sample). The score of 0 = pattern N > 70%; 1 = patterns N + P > 70%; and 2 = pattern A ≥ 30%. The receiver operating characteristic (ROC) curve was used to evaluate the predicted value of DNAI1 score for AR.Results: The ciliary length was reduced by 33.3% in patients with AR compared with controls (P < 0.0001). The higher DNAI1 score was found in the AR group, with a median (first and third quartile) of 0.9 (0.4 and 1.08), which was 0.1 (0 and 0.76) in the control group (P = 0.0071). The ROC of DNAI1 was calculated based on the area under the curve of 0.74 (P = 0.0094). The cutoff value of ROC was 0.5833, with a sensitivity and specificity of 70%.Conclusion: These results suggested that the shorter ciliary length and aberrant localization of DNAI1 are potentially important pathological characteristics of the allergic nasal mucosa. The aberrant localization of DNAI1 may provide a novel candidate target for clinical management of AR.Keywords: allergic rhinitis, cilia length, DNAI1, biomarker, ciliated marker